2022
DOI: 10.3390/w14121911
|View full text |Cite
|
Sign up to set email alerts
|

Study on Index of Groundwater Ecological Function Crisis Classification and Early Warning in Northwest China

Abstract: The natural oases in the plain area of the northwest inland basin strongly depend on the groundwater depth. With the overexploitation and utilization of groundwater, natural oases are faced with the problems of serious degradation and rehabilitation. How to evaluate the degree of the degeneration crisis of groundwater ecological function has become one of the key scientific and technological problems to be solved. In this paper, the Shiyang River basin of Gansu Province was selected as a typical research area.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In this study, the maximum value of NDVI was measured in the groundwater depth of 3-5 m, followed by 2-3 m. When the groundwater depth was greater than 6 m, the value of NDVI was less than 0.2, and with increases in the groundwater depth, NDVI continued to decrease. In the research on the relationship between vegetation growth and groundwater depth response in the arid zone, it has also been shown that the reasonable threshold for the appropriate growth of vegetation crops in the arid zone is 3-5 m [52], and the vegetation begins to suffer from growth stress at a depth of 6 m in the groundwater depth [38,53,54]. the risk of soil salinization into the analysis of the ratio of suitable wells and canals for combined irrigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the maximum value of NDVI was measured in the groundwater depth of 3-5 m, followed by 2-3 m. When the groundwater depth was greater than 6 m, the value of NDVI was less than 0.2, and with increases in the groundwater depth, NDVI continued to decrease. In the research on the relationship between vegetation growth and groundwater depth response in the arid zone, it has also been shown that the reasonable threshold for the appropriate growth of vegetation crops in the arid zone is 3-5 m [52], and the vegetation begins to suffer from growth stress at a depth of 6 m in the groundwater depth [38,53,54]. the risk of soil salinization into the analysis of the ratio of suitable wells and canals for combined irrigation.…”
Section: Discussionmentioning
confidence: 99%
“…(2) The vegetation cover of the Weigan River irrigation district from 2012 to 2021 gen- According to the "Survey and Evaluation Report of Planned Groundwater Resources in the Weigan River Basin of Aksu Region, Xinjiang", Populus euphratica is the main ecological forest plantation species in the study area. The suitable groundwater depth for Populus euphratica is 3-5 m, and its stress water level is 6-8 m [54]. This is generally consistent with the pattern depicted in Figure 11, where NDVI shows a positive correlation with groundwater depths below 4 m and NDVI shows a negative correlation with groundwater depths above 4 m. Due to the low rainfall in arid areas such as the study area, groundwater is an important resource for supporting the growth of vegetation; however, the uncontrolled exploitation of groundwater will inevitably destroy the stability of the groundwater flow field in the natural vegetation area, meaning that the depth of the groundwater will continue to increase, resulting in drought stress of natural vegetation and even large-scale extinction [51,54].…”
Section: Discussionmentioning
confidence: 99%
“…The over-exploitation of groundwater causes a decline in the water table, leading to an accumulation of soil salts and toxins, especially in drought years, in areas of high agricultural activity and increased water stress [15][16][17][18][19][20][21][22]. In China, the relationship between vegetation and groundwater burial depth, as well as the water table, water quality, and soil, has been studied in the Tarim River [23], Hei River [24], Shiyang River Basin [25,26], Sanguang River [27], Inner Mongolia Loop [28], Loess Plateau [29], Hulunbeier in Inner Mongolia [30], Ejina [31], and Gurbantunggut Desert [32,33]. Such studies have provided theoretical support for protecting the stability of vegetation in arid and semi-arid regions.…”
Section: Introductionmentioning
confidence: 99%
“…Affected by changes in the natural environment and by human activities, the groundwater level in the Shiyang River Basin has dropped significantly in recent decades [11][12][13]. This lower groundwater level has resulted in a series of ecological and environmental problems such as water quality deterioration, vegetation decline, land desertification, and a decrease in the area of the spring water overflow zone [14]. A series of water transfer projects, including the water transfer from the Yellow River to the Jingdian phase II project and the water transfer from the upstream Xiying River, have been carried out in this basin since 2001.…”
Section: Introductionmentioning
confidence: 99%